Vaccine strategies for cancer prevention in Lynch syndrome: the potential of dendritic cell-based therapy - Romy N. Kuipers; Mark A. J. Gorris; Cristina Bayó; Tom Hofland; Daniel Benítez Ribas; Georgina Flórez Grau; Nicoline Hoogerbrugge; Joaquin Castillo; Francesc Balaguer; Tanya M. Bisseling; Gerty Schreibelt; I. Jolanda M. de Vries (Familial Cancer, 2026)
Cancer vaccines offer a promising strategy for cancer prevention, particularly in hereditary cancer syndromes such as Lynch syndrome (LS). LS is characterized by a high lifetime risk of developing various malignancies due to defects in DNA mismatch repair, leading to an accumulation of mutations, particularly frameshift insertion/deletions (indels) within microsatellite loci. These indels create shared tumour-specific neoantigens, which are unique to LS and can be recognized by the immune system and trigger cancer cell killing. Importantly, these neoantigens are also present in precancerous lesions, making LS an ideal target for immune-interception strategies aimed at prevention. Over the years, a variety of vaccine designs targeting different antigens along with a range of delivery platforms have been explored for different types of tumours, each with its own advantages and limitations. In this review, we provide an overview of the key antigens and delivery platforms used in cancer preventive vaccine development for LS, evaluate their limited clinical outcomes to date, and explore the future directions of preventive vaccine immunotherapy. A particular focus is placed on the promising potential of dendritic cell vaccination therapy as a future approach in this field.